Some Turkish Documents About the Monastery MilešEvo (Prilozi za orijentalnu filologiju, 2017)
Some Turkish documents concerning the legal position of the monastery Mileševo and its monks are reviewed. They also enlighten the attitudes of the. Ottoman authorities, both central and local, toward the monks, and the relations between the local inhabitants and the monks.The documents are from the period between 1469. and 1614, and they include parts of four tahrir defters (the Turkish registers) and two documents from the so-called muhime defters. From the tahdr defters we can see the number of monks, ·the size of their property and their annual taxes in the years the defters are from (1469, 1477, 1515. and 1585). The muhilme defters are from 1589. and 1614. and they show clearly the attitudes of the central authorities in some proprietary and legal questions related to this monastery and its monks.Taken together, the documents give some new data rubout the life and the activity of the monastery Mileševo at the end of the XVth and in the XVIth century. They contribute to the more comprehensive understanding of the legal position of the church in the Ottoman Empire.